GERAKAN ANTIPENYERAHAN DI SARAWAK, 1946-1949: PENENTANGAN ORANG MELAYU TERHADAP PENJAJAH BRITISH (The Anti-Cession Movement in Sarawak, 1946-1949: The Malays Resistance Against the British Colonial) - Hui Ling, Ho (Journal of Al-Tamaddun, 2019)
This study aims to examine the struggle of the Malays against the British colonial through the anti-cession movement from 1946 to 1949. After the Japanese occupation, the Sarawak’s political status changed from a British protectorate to a Crown Colony on 1 July 1946. Situation of Sarawak in the aftermath of the Japanese occupation and the personal problems faced by Vyner Brooke forced the Raja to dissolve the Brooke administration. For the Britain, it was a long-awaited opportunity to exert their control over Sarawak. This transition, however, did not take place smoothly. The people of Sarawak especially the Malays were not prepared to accept the imminent change of political status of Sarawak, thus leading to an anti-cession movement. In this study, the approach used is based on archives and library researah by examining the primary and secondary sources. The findings show that the Malays played an important role in the anti-cession movement. The movement fought against the British attempt to govern Sarawak and, instead, strived for a grant of self-government. The various strategies were undertaken to thwart the plans of Raja Brooke and the British. Although the anti-cession movement eventually failed to achieve its objective of preserving Sarawak’s independence, it nevertheless had raised the national consciousness and political awareness among the Malays in Sarawak. Sarawak was colonized by the British until 16th September 1963.